Death and Divorce (Divorce by Death) from Legal, Religious, Ethical, and Social Perspectives: A Multidisciplinary Analysis for Public Education - Yonas PAP; Musa Darwin Pane; Solihin Bin Nidin; Samikshya Madhukullya (Faculty of Law, Universitas Pekalongan, 2025)
Death as a cause for the dissolution of marriage has been recognised in Indonesian family law, religious traditions, and customary practices, but its legal implications are often controversial especially in childless marriages because the lack of clarity regarding post-death authority often triggers disputes over funeral arrangements, burial locations, and inheritance. This study uses qualitative normative legal research with a comparative-integrative design. The corpus includes legislation (UUP No. 1/1974, KHI, Civil Code) and court decisions, religious texts and contemporary interpretations (Islamic–Christian), journal articles from 2021–2025 on the themes of grief/funeral rites/family relations, BPS data, and media documents. The analysis was conducted through doctrinal legal analysis, hermeneutics, content analysis and reflective thematic analysis, synthesised with a convergent-integrative model. The findings confirm a declarative–operational gap: the law states that death ends a marriage, but does not regulate in detail the authority to manage the body, determine the location, and conduct rites; this void is filled by customary/kinship claims that often marginalise spouses, especially widows in a patriarchal context. Theologically, there is consistency in respect for spouses, but cultural practices are not always in line with this. The consequences are damage to dignity, prolonged grief, and weakened community cohesion. This paper contributes an integrative framework of law, religion, ethics and society, an operational glossary, and a draft Post-Death Authority Determination Form (POP-K). Recommendations include implementing regulations that establish a hierarchy of authority with spouses as the primary holders (unless there is an authentic will), inter-agency SOPs, multi-level community mediation, and protection clauses for childless marriages. These findings reinforce the agenda of public literacy and dispute prevention.